Faktor-Faktor Yang Mempengaruhi Nilai Perusahaan - Bernhard Wilfridus, Liana Susanto (Jurnal Paradigma Akuntansi, 2021)
The purpose of this research is to obtain empirical evidence about the influence of profitability, leverage, asset growth, and firm size toward firm value in manufacturing companies listed in Indonesian Stock Exchange during the period of 2016-2018. This research used 73 samples of manufacturing companies that have been selected using purposive sampling method. Data processing technique in this research using program EViews 11th version. The result of this research indicate that all independent variables used in this research simultaneously have a significant effect on firm value. The result of partially test indicate that profitability, and leverage have an significant effect on profitability, while asset growth, and firm size have an insignificant effect on frim size.